Rural Wages during industrialization in Chile: economic and institutional factors - Reyes Campos, Nora (Estudios de Economía, 2016)
The role of the agricultural sector during the ISI period and the debate about the agricultural wage and the living conditions of the farm workers have a long historiography. But until today there is little information about workers' income in the long run. In this paper we want to reflect about the wage level reached during this period and for that we will present a new wage series for 1934-1973. We seek to analyze their behavior considering the sector labour productivity, its relation with industrial wages and the institutional frame in this period.